2019
DOI: 10.1093/pch/pxy191
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing a preprinted order form for inpatient management of otherwise healthy children admitted to a tertiary care centre with a diagnosis of bronchiolitis

Abstract: Objective To examine the effect on length of stay (LOS) of a preprinted order (PPO) set for children admitted to hospital with a diagnosis of bronchiolitis, as well as on quality improvement measures, medical errors, and resource utilization. Patients and methods A retrospective chart review was performed of children admitted to the inpatient units at the Children’s Hospital of Eastern Ontario (CHEO) with a discharge diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A 2014 systematic review of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements . Such QI efforts constitute 1 factor potentially associated with the decline in nonrecommended services found across our study period.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A 2014 systematic review of 14 published QI initiatives in inpatient bronchiolitis care found that these interventions were associated with reductions in bronchodilator, steroid, antibiotic, and CR use. The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements . Such QI efforts constitute 1 factor potentially associated with the decline in nonrecommended services found across our study period.…”
Section: Discussionmentioning
confidence: 82%
“…The QI efforts included in this review or published after the review have been associated with reduced use of nonrecommended services by implementing local clinical pathways citing AAP recommendations [19][20][21][22][23][24][25][26][27][28][29] ; international studies using other national guidelines as the basis for local improvements have been associated with similar improvements. [30][31][32][33] Such QI efforts constitute 1…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%